Effects of pre-cementation cleaning protocols on bond strength of indirect composite resin restorations contaminated with saliva. (Applied Sciences in Dentistry, 2021)
Objective: Compare the effects of different pre-cementing cleaning protocols on adhesive bond strength (MPa) in indirect composite resin restorations contaminated with saliva. Materials and Methods: 110 tests bodies of indirect composite resin, divided into 2 groups: with no contamination (NC); with contamination (WC); distributed in 22 subgroups (n = 5) according to the Ultrasound (U) variables; Cleaning Paste (CP); Ethanol 96 ° (E), Application times: 5-20-30-180s. Five cylinders (1mm high x 0.7 Ø) of cement (Variolink Esthetic LC) per sample made on treated and light-cured surfaces (20s). After 24hrs / 37ºC + distilled water, they were subjected to the RUA test (0.5 mm / min) until fracture point in a universal test machine. Analyzed with one-way ANOVA and post hoc Tukey test (α = 0.05).Results: Contaminated CP30’’ was the protocol with the highest binding resistance (14.57 ± 1.01) (p